Assessment of glycine derivative N-benzylidine-2((2-oxo-2-(10H-phenothiazine-10yl)ethyl)amino) acetohydrazide as inhibitor for mild steel corrosion in 1 M HCl solution: electrochemical and theoretical approach. Issue 3 (1st February 2018) - Zehra, Saman; Mobin, Mohammad; Aslam, Jeenat; Parveen, Mosarrat
Abstract: Corrosion is a severe challenge which restricts the use of mild steel (MS) in various application where it comes in contact with aggressive chemicals and conditions. In this regard, different inhibitors were chosen, but environment unfriendliness of such inhibitors is a primary cause of concern. In this study, we present the systematic investigation of an environmentally benign compound, a glycine derivative N-benzylidine-2((2-oxo-2-(10H-phenothiazine-10yl)ethyl)amino) acetohydrazide (BPAA), as potential corrosion inhibitor at different temperature (30, 40, 50, and 60 °C). The investigation is accomplished by using the techniques including electrochemical polarization, electrochemical impedance spectroscopy (EIS), gravimetric, UV-visible spectrophotometry, FT-IR spectroscopy. The morphological characterization of the samples has been done by using high resolution SEM. The evaluated compound works as effective inhibitor for acid corrosion at substantially lower concentration and its adsorption on the MS surface was found to followed the Langmuir adsorption isotherm. Calculated thermodynamic parameters for adsorption unveiled a strong interaction amongst the inhibitor-MS surface. The electrochemical results revealed that the inhibitor act as mixed-type. The corrosion inhibition efficiency (IE) of the inhibitor was synergistically enhanced in the presence of surfactant additives sodium dodecyl sulfate and cetyl pyridinium chloride at quite lower concentration and showed that the addition of surfactant is an alternate strategy to enhance the IE and reduce the cost. The order of IE acquired from experimental results is successfully verified by theoretical calculations.